Information items used by online fraudsters and its relationship to Indonesian digital literacy - Ardoni Ardoni (Berkala Ilmu Perpustakaan dan Informasi, 2022)
Introduction. This research was conducted to examine the information items used by online fraudsters related to the level of digital literacy of the society. This research was done on the pillars of data security in digital literacy. Data Collection Methods. Data was collected by watching videos on Youtube, online interviewing people who complained about the fraud they experienced on Facebook and Whatsapp in the period of 2019-2022. Data Analysis. The data was descriptively analyzed and classified to describe information items used by the fraudsters. Results and Discussion. The items used by the fraudsters are banking service terms, real but fake URLs, police standard operating procedures, and English terms used by market place. Therefore, continuous socialization from institutions related to these items of information is needed to improve digital literacy of society which has the potential to cause financial losses. In terms of socialization, libraries can play a proactive role. Conclusion. Information items that often used by online fraudsters are information related to banking services, police, marketplace, and fake social media accounts. This research may be continued to understand how low the victims' ignorance about the information items.